Odpowiedzi

Najlepsza Odpowiedź!
2010-03-11T16:31:19+01:00
A.) 11/15x + 1/5 =3/*15
11x+3=45
11x=45-3
11x=42/:11
x=42/11= 3 9/11
b.) 0,4z - 1 = 0,5
0,4z=0,5+1
0,4z=1,5/:0,4
z= 15/10*10/4= 15/4= 3 3/4
c.) 5/6y - 0,5 = 0,25y - 2/3
5/6y-0,25y=0,5-2/3
20/24y-6/24y= 3/6-4/6

14/24y=-1/6/*24/14
y= -4/14=-2/7
1 5 1
2010-03-11T16:56:07+01:00
A) ¹¹/₁₅ x + ⅕ = 3
¹¹/₁₅x = 3 - ⅕
¹¹/₁₅x = 2⅘
x=(2⅘:11)*15
x=¹⁴/₅₅*15
x=3⁹/₁₁

b)0,4z -1 = 0,5
0,4z=0,5+1
⅖z=1,5
⅕z=0,75
z=0,75*5
z=3,75

c)⅚y-0,5=0,25y-⅔
⅚y-¼y=½-⅔
¹⁰/₁₂y-³/₁₂y=³/₆-⁴/₆
⁷/₁₂y=-⅙
y=(-¹/₆:7)*12
y=-¹/₄₂*12
y=-²/₇